2022
DOI: 10.1111/jgs.17977
|View full text |Cite
|
Sign up to set email alerts
|

The association of a frailty index from laboratory tests and vital signs with clinical outcomes in hospitalized older adults

Abstract: Background Frailty, a state of vulnerability to stressors resulting from loss of physiological reserve due to multisystemic dysfunction, is common among hospitalized older adults. Hospital clinicians need objective and practical instruments that identify older adults with frailty. The FI‐LAB is based on laboratory values and vital signs and may capture biological changes of frailty that predispose hospitalized older adults to complications. The study's aim was to assess the association of the FI‐LAB versus VA‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…The third aspect of remarking is the relationship between frailty and all-cause mortality. Investigations have shown that high and moderate FI-LAB scores were associated with worse in-hospital and post-hospital outcomes, and FI-LAB can stratify older adults at increased risk of death alone [ 25 ], we proved this. According to a study using a large general older population hospitalized for pneumonia, frailty, measured by the Hospital Frailty Risk Score, was associated with mortality [ 26 ].…”
Section: Discussionsupporting
confidence: 55%
“…The third aspect of remarking is the relationship between frailty and all-cause mortality. Investigations have shown that high and moderate FI-LAB scores were associated with worse in-hospital and post-hospital outcomes, and FI-LAB can stratify older adults at increased risk of death alone [ 25 ], we proved this. According to a study using a large general older population hospitalized for pneumonia, frailty, measured by the Hospital Frailty Risk Score, was associated with mortality [ 26 ].…”
Section: Discussionsupporting
confidence: 55%
“…Several studies have shown that frailty is predictive of worse outcomes in many different medical fields including general clinical outcomes for hospitalized older adults [ 16 ], neurosurgical outcomes in patients with brain tumors [ 17 ], older patients with trauma undergoing surgery [ 18 ], and older patients undergoing general surgical procedures [ 19 ]. Relatively few studies have delved into the impact of preoperative frailty on outcomes in urological conditions, rendering our study novel.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the intermediate and high frailty risk groups had a significantly higher risk of any complication (aOR = 3.27, 95% CI: 2.98-3.60, p < 0.001; aOR = 8.52, 95% CI: 7.69-9.45, p < 0.001, respectively). For specific complications, the intermediate and high frailty risk groups general clinical outcomes for hospitalized older adults [16], neurosurgical outcomes in patients with brain tumors [17], older patients with trauma undergoing surgery [18], and older patients undergoing general surgical procedures [19]. Relatively few studies have delved into the impact of preoperative frailty on outcomes in urological conditions, rendering our study novel.…”
Section: Associations Between In-hospital Outcomes and Hfrs-defined F...mentioning
confidence: 99%
See 1 more Smart Citation
“…BMI, body mass index. The median (IQR) hospital stay duration was 10 (8-14), 13 (9-17) and 14 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) days for the robust, prefrail and frail groups, respectively. The frail group had a longer hospital stay than the robust and prefrail groups (P adj <0.001, P adj =0.007, respectively).…”
Section: Open Accessmentioning
confidence: 99%